2017
DOI: 10.1186/s12987-017-0068-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of shear stress on iPSC-derived human brain microvascular endothelial cells (dhBMECs)

Abstract: BackgroundThe endothelial cells that form the lumen of capillaries and microvessels are an important component of the blood–brain barrier. Cell phenotype is regulated by transducing a range of biomechanical and biochemical signals in the local microenvironment. Here we report on the role of shear stress in modulating the morphology, motility, proliferation, apoptosis, and protein and gene expression, of confluent monolayers of human brain microvascular endothelial cells derived from induced pluripotent stem ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
125
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 134 publications
(164 citation statements)
references
References 76 publications
10
125
2
Order By: Relevance
“…Regarding leukocyte trafficking and other BBB properties, it has been found that inducing shear stress, which is normally encountered as a result of blood flow across brain endothelial cells in vivo, can cause some important changes in BEC phenotype. For example, sheer stress induced higher TEER, mRNA upregulation of TJPs and BBB transporters, as well as increased expression of mRNA levels of cell adhesion molecules such as VCAM-1, ICAM-1, and PECAM [98]. In contrast, P-and E-selectin mRNAs were decreased, which may further indicate a BBB phenotype since BECs lack P-and E-selectins in their Weibel-Palade bodies at baseline [99].…”
Section: Axis 4-immune Cell Trafficking Between Blood and Brainmentioning
confidence: 98%
“…Regarding leukocyte trafficking and other BBB properties, it has been found that inducing shear stress, which is normally encountered as a result of blood flow across brain endothelial cells in vivo, can cause some important changes in BEC phenotype. For example, sheer stress induced higher TEER, mRNA upregulation of TJPs and BBB transporters, as well as increased expression of mRNA levels of cell adhesion molecules such as VCAM-1, ICAM-1, and PECAM [98]. In contrast, P-and E-selectin mRNAs were decreased, which may further indicate a BBB phenotype since BECs lack P-and E-selectins in their Weibel-Palade bodies at baseline [99].…”
Section: Axis 4-immune Cell Trafficking Between Blood and Brainmentioning
confidence: 98%
“…Utilizing this capability, several groups have lined microfluidic devices with iBMECs to study the cellular response to flow-induced shear stress. Using a PDMS-based platform with shear rates up to 12 dyne/cm 2 , investigators determined that iBMECs do not elongate or align with the direction of fluid flow in response to shear stress, a phenotype unique to endothelial cells of the brain [60]. Expanding on these observations, subsequent studies showed that while iBMECs do not change their morphology in response to shear stress, they do respond at the transcriptional level in a force-dependent manner [31].…”
Section: Ipsc-derived Microfluidic Chip Models Of the Bbbmentioning
confidence: 99%
“…Several groups have made progress in this area by exposing iBMECs to hypoxia [19], modifying extracellular matrix composition and stiffness [62], or by optimizing hydrogel scaffolds and fluid flow parameters that allow for maintenance of barrier properties for up to 3 weeks [63]. Many of the BBB-chip platforms developed and optimized recently are now being used to investigate drug permeabilities [19,31,64,65], neurodegenerative disease [31,43,66], and other functional aspects of the BBB [33,60,61,67].…”
Section: Ipsc-derived Microfluidic Chip Models Of the Bbbmentioning
confidence: 99%
“…In addition, the cellular uptake, transport via the transcellular/paracellular routes and drug-release kinetics, needs to be evaluated. Various device geometries have been reported for brain vasculature models (Figures 2 and 3); parallel channels (PCs), with interconnecting micro-gaps, [42][43][44][45]51,56,90], hollow-microtubes (HTs) [2,47,49,50,52], and others, concentric-ring (CR) channels [54], multi-layered channels [53], hybrid-microchambers [57], and microwells [58]. Each of the above designs has its own advantage in terms of angiogenesis drug screening application.…”
Section: Angiogenic Nanomedicine Screening In Locsmentioning
confidence: 99%
“…Unlike in the static petri dish culture, dynamic flow and shear stress can be generated on microfluidic platforms. LOC provides precise control over the flow rate and shear stress when integrated with a syringe pump [90]. In an LOC, it is possible to dynamically flow culture media and other fluids at a physiological flow rate and create shear stress on the BMVECs (6 dyne cm −2 at 100 µL h −1 ).…”
Section: Dynamic Flow and Shear Stress In Brain-angiogenesis Locsmentioning
confidence: 99%